Diagnosis and treatment of bronchial Dieulafoy’s disease: a case series - Yang, Huizhen; Liu, Yuyan; Lou, Jianghua; Chen, Xianliang; Zhang, Quncheng; Zhang, Xiaoju; Herth, Felix (Respiration, 2025)
Introduction: Bronchial Dieulafoy’s disease (BDD) comprises rare vascular malformations. This study analyzes a series of BDD patients diagnosed through combined bronchial computed tomography arteriography (CTA) and bronchoscopy, addressing critical gaps in diagnostic standardization and therapeutic decision-making. Methods: This was a retrospective review of patients who underwent CTA and bronchoscopy for mild to massive and unexplained recurrent hemoptysis in two centers during a 6-year period. Results: Thirty-six patients were diagnosed with BDD by bronchial CTA and bronchoscopy. Abnormal vessels were observed by CTA in all 36 patients; twisted vessels protruding into the bronchial lumen were found in 14 patients. Mucosal eminence lesions in the ipsilateral lobar/segmental bronchus were detected by white light bronchoscopy in all patients. Bronchial artery embolization (BAE) was performed in 10 patients, and endobronchial intervention was attempted in 18 patients as the initial treatment. Eight patients received application of antibiotics and hemostatic drugs, only. Recurrent hemoptysis occurred in 1 patient. Conclusion: Vascular disease was the main cause of large to massive hemoptysis. CTA is a noninvasive method that could be used for first-line screening for bronchial vascular malformations. Bronchoscopic procedures could confirm the diagnosis of BDD. BAE is often the first choice, clinically, owing to the invasiveness of thoracic surgery and the patient’s status. Bronchoscopic interventional therapy is an effective complement to BAE.